2019
DOI: 10.15390/eb.2019.7897
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Parents’ Digital Parenting Efficacy through Several Demographic Variables

Abstract: Dijital teknolojilerin gelişmesiyle yaşamın her alanında kolaylıklar yaşanmaya başlamıştır. Bu teknolojiler, kolaylıkların yanı sıra riskleri de beraberinde getirmektedir. Zararlı içerikler, siber zorbalık, pornografi, cinsel içerikli mesajlar gibi riskler dijital araçlarla birlikte evlere kadar rahatlıkla girebilmektedir. Bu risklerden en çok etkilenmesi beklenen grup çocuklardır. Çocukların gelişiminden birinci derecede sorumlu olan ebeveynlere bu noktada önemli sorumluluklar düşmektedir. Ebeveynler, çocukla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In addition, the level of digital literacy of parents, their ability to manage digital security and active communication with children regarding the use of digital devices are indicators of supporting digital parenting self-efficacy. This indicator did not differ based on the role of parents in the process, Internet use, socio-economic status, occupation and educational level (Yaman et al 2019).…”
Section: Parents' Approaches To Digital Parenting During the Pandemicmentioning
confidence: 77%
“…In addition, the level of digital literacy of parents, their ability to manage digital security and active communication with children regarding the use of digital devices are indicators of supporting digital parenting self-efficacy. This indicator did not differ based on the role of parents in the process, Internet use, socio-economic status, occupation and educational level (Yaman et al 2019).…”
Section: Parents' Approaches To Digital Parenting During the Pandemicmentioning
confidence: 77%
“…We classi ed the results from the studies involving the conscious use of applications on smart devices. Our classi cation was (1) knowing about applications (Authors, Yaman et al, 2019). This classi cation served as the theoretical model for the scale we developed.…”
Section: Discussionmentioning
confidence: 99%
“…(1) fostering awareness between collocated family members, (2) (Yaman et al, 2019) in the literature. There was no study aimed at measuring parents' knowledge and awareness of the conscious use of applications on smart devices among these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, other research concluded that people of African descent are vulnerable to cyberbullying in host countries where they are seen as groups of lesser value threatening finances, culture, national identity, or civil insecurity (Rodríguez-Hidalgo et al, 2018). These groups have in common being minorities in the populations analyzed (Blaya and Audrin, 2019), which highlights the need to detect this type of cyberbullying in adolescents of these groups for future social integration in adulthood (Yaman et al, 2019), for them to be part of democratic, plural, and inclusive societies (Kislyakov et al, 2021;Meter et al, 2021).…”
Section: Introductionmentioning
confidence: 98%